Claim Control Strategies in National Health Insurance: A Scoping Review - Syarifah Zulinar; Sutopo Patria Jati; Septo Pawelas Arso (UNIVED Press, 2025)
Pending and rejected claims within national health insurance systems remain a global concern, particularly in developing countries. This scoping review aims to explore the strategies implemented by various countries to manage their health insurance claims and reduce the occurrence of pending and rejected cases. The protocol of the study has been registered through Open Science Framework (OSF) with this link https://doi.org/10.17605/OSF.IO/BPQYA. The review analyzed articles published from 2016 to 2025 and retrieved from PubMed, Science Direct, Wiley, ProQuest, and Google Scholar databases. Of the 699 titles initially identified, 11 relevant articles were included in the final analysis, originating from India, Tanzania, Ghana, and Indonesia. The results indicate that pending and rejected claims are a common challenge in developing countries, predominantly due to human-related factors, such as input errors, coding inaccuracies, and insufficient training. Implemented strategies to address these issues include utilising blockchain technology, digitization and automation, standardization of processes, capacity building for human resources, coordination among stakeholders, adaptive policy implementation, and cost-efficiency measures. In Indonesia, manual verification is still considered an effective method for reducing problematic claims. The study concludes that training for claim administrators and further research into digital innovations, including blockchain, are essential for optimizing claim management.